From Magas to Glaukon: The Long Life of Glaukon of Aithalidai and the Chronology of Ptolemaic Re-Annexation of Cyrene (ca. 250 BCE) - Rosamilia, Emilio (Chiron. Mitteilungen der Kommission für Alte Geschichte und Epigraphik des Deutschen Archäologischen Instituts, 2021)
The death of king Magas around the mid-third century BCE left Cyrene in a state of civic turmoil. Various factions and people took control of the city before Ptolemy II re-annexed it near the end of his reign. Although both the sequence and the dating of these events are still debated, an inscription sheds new light on the history of mid-third-century Cyrene. A closer look at a fragmentary catalogue of eponymous priests of Apollo dating from the same period shows that a few names are compatible with Ptolemaic commissioners who seem to have held the priesthood for a few years in a row. Among them, one name stands out: [Glau]kon son of Eteokles. This Athenian statesman was the younger brother of the famous Chremonides of Aithalidai, after whom the Chremonidean war is named. Therefore, an analysis of all available sources on Glaukon’ s life provides new data on the chronology of events in mid-third-century Cyrenaica as well as Glaukon’ s presence in the region and death.